KELAYAKAN MEDIA POSTER PERILAKU MAKAN PADA SUBMATERI ZAT MAKANAN DI KELAS XI SMA - Desta Rotuana Sihombing; Wolly Candramila; Reni Marlina (Universitas Tanjungpura, 2019)
AbstractThis study aimed to determine the feasibility of poster as a instructional tool in the Sub Material of Food Substance in second grade of high school. This was a descriptive research and data collection was done by distributing validation questionnaire to five experts on the aspects of format, content, language and practicality. The feasibility assessment was carried out by 5 validators consisting of 2 lecturers in the Study Program of Biology Education in FKIP University of Tanjungpura Pontianak and 3 high school biology teachers, namely SMAN 1 Bonti, SMAN 2 Sungai Raya and SMAN 2 Sungai Ambawang. The validity test resulted in that poster was feasible to be used as a learning medium based on 12 out of 13 indicators with a CVI = 0.96. In this case, poster repairs should be done in format aspect in which poster size should be made larger so that it can be used for individuals, small groups and the whole class. Keywords: Feasibility, Food Substances , Pictorial Story,